Comment on oscillatory optical and acoustical radiation pressure. (October 2020) - Marston, Philip L.
Highlights: Introductory review of modulated optical and acoustical radiation pressure. Distinguishes double-sideband suppressed carrier modulation from conventional amplitude modulation and notes their relative advantages. Explains motivation for introducing modulated acoustical radiation pressure to measure droplet and bubble modes. Makes connections with acoustical and optical levitation. Makes up for some deficiencies of a recent JQSRT publication. Abstract: This comment is timely because of a paper [JQSRT 250 (2020) 106994] on the time dependence of optical radiation forces resulting from modulated illumination. While the acoustic analog of oscillatory radiation pressure was mentioned, the omission of early developments contributes to the introduction of terminology that is not sufficiently descriptive. For example, the illumination considered was double-sideband suppressed carrier modulation (DSB-SCM), as distinct from conventional "amplitude modulation" (AM), contrary to the impression given. Properties of DSB-SCM and AM radiation pressure are reviewed along with some early acoustical and optical modulated radiation pressure experiments, selected recent research, and some analytical and related concerns.